Clinical Study of Association of Diabetic Retinopathy with Diabetic Nephropathy (Medical Forum Monthly, 2022)
Objective: To determine whether or not patients with diabetic retinopathy (DR) have nephropathy or neuropathy, and to establish a link between the severity of DR and the presence or absence of either.Study Design: Prospective, hospital-based, non-interventional studyPlace and Duration of Study: This study was conducted at the Peoples University of Medical Sciences for Women Shaheed Benazir Abad Sindh, from January 2019 to November 2020.Materials and Methods: Patients with diabetes mellitus (DM) for at least five years who gave their informed consent to participate in the research were eligible to participate were included in this study. According to Early Treatment Diabetic Retinopathy Study categorization, the patient was diagnosed with DR. Urine albumin creatinine ratio and estimated glomerular filtration rate were used to determine the severity of diabetic nephropathy. Diabetic neuropathy severity was determined by the speed of nerve conduction.Results: A total of 70 patients were enrolled in this study. DR severity appears to be linked to DN severity. There was a statistically significant (P<0.05) link between the severity of DR and the stage of DN (U ACR staging). There was a statistically significant correlation (P<0.05) between the severity of diabetes and the severity of diabetic nephropathy. Diabetic neuropathy was found to be unrelated to the severity of DR.Conclusion: An indicator of future renal disease development as well as an indicator of neurological outcomes in diabetic patients may be found in the relationship between DR severity and the severity of both diabetic nephropathy and diabetic neuropathy.